Influence of Age on Oral Hygiene Status in Out patients Attending a Private Dental Institution - A Retrospective Study - FATHIMA, FAAZILA; LEELAVATHI, L.; P, SENTHIL MURUGAN (The journal of contemporary issues in business and government, 2021)
Effective and efficient oral hygiene practices are essential tools for achieving good oral health. Even though the value of good oral hygiene practices has increased over the years, many studies state that poor oral hygiene levels is still highly prevalent. Preventive strategies, both at individual and population level will help to reduce the negative impact of oral hygiene on oral and general health. The aim of this study is to evaluate the association between age and oral hygiene among outpatients who reported to a private dental college and hospital. It is a university setting study. About 7987 adult patients who reported to the dental college were included in the study. The data of the oral hygiene index simplified (OHIS) of these patients were collected from patient records. The data was entered in excel and imported to SPSS software for statistical analysis. Descriptive statistics and Chi-square test was used for analyzing the data. From the results, it was observed that as age increased OHIS score also increased. OHIS score of good was prevalent in 38.2% of the study population, fair OHIS score in 56.4% and poor OHIS score in 5.4% of the outpatients. Fair OHIS(56.4%) score was the most prevalent among the study population. Age wise comparison of OHIS score revealed that fair and poor OHIS scores was most prevalent among outpatients above 55 years old and this was found to be statistically significant. This study concludes that poor OHIS scores was more prevalent among study participants above 55 years when compared to other age groups.